Una charca marina - Gunzi, Christiane; Greenaway, Frank (Madrid : Anaya, 1993)
Discusses the animals and plants that live in saltwater tidal pools. Includes anemones, snails, crabs, starfish, and marine plants.
Translation of: Rock pool.
Includes index.
Keywords: Seashore ecology; Tide pool ecology